Budaya Patriarki dalam Lingkup Masyarakat Menengah ke Bawah dalam Pandangan Feminisme Eksistensialis Simone de Beauvoir - Jihan Audi Clarissa (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to discuss patriarchal culture in the lower middle class society in the view of Simone de Beauvoir's existentialist feminism. This study uses a qualitative approach by applying a descriptive-analytical method. The formal object of this research is Simone de Beauvoir's existentialist feminism, while the material object is patriarchal culture. The scope of research is the lower middle class society. The results and discussion in this study indicate that patriarchal culture is formed from social construction from time to time. This research concludes that there is no impossibility for us to fight for justice and rights and tear down the thick patriarchal culture in our society.